#TITLE_ALTERNATIVE# - EKAVIENAMUKTI RESTIWULAN (NIM 23409043); Pembimbing : Dr. Ir. Herman Rahadian Soetisna , AYU
Recently, many companies are ignoring a factor of a worker capability in having a concentration as a source for analyzing a working system improvement. Eventhough many companies has providing a time break to have a res during a working hours or implement a work shift time, however the determination to decide the break time or shift time are not sufficient with the capability of the worker in maintaining the level of his concentration. Therefore it is required to have an information system regarding to a level of worker concentration, which also provide list of options in measuring, managing, and analyzing the result of its measurement. This research is developing the software for information system of a worker concentration. The first phase, which has to be done is developing an information system is by using FAST (Framework for the Application of Thinking System) method, whereas it consist of seven phase. They are, scope definition, problem analysis, requirement analysis, logic design, decisions analysis, construction and implementation (concentration measurement). The result measurement trough the software can be directly stored in database system, and can be directly analyzed. At the second phase, which has to be done, is an implementing usability test, which consist of nine phase, they are, problem analysis, objective, user profile, usability test method, listing of the assignment, environment and instrument test, researcher responsibility, measurement and test report. The information system wich being developed in this regard, in adjacent to a simple way to do, also very efficient and effective, it was due to the capability of the system to measure the level of concentration of the worker, to manage the data of the result of the measurement, to provide a various of menu to analyze the level concentration of the worker, furnish with an information on every single menu and help menu. The information system wich is being developed can be used to analyze whether the working duration, length of working break time, number working break, length of break time and working shift has already implemented in accordance with the capability of the workerÃ‚Â’s in a good concentration